THE RELATIONSHIP BETWEEN ORGANIC MATERIAL CONTENT IN SEDIMENTS AND THE ABUNDANCE OF EPIPELIC DIATOMS IN THE INTERTIDAL ZONE OF THE WATERS OF DUMAI CITY, RIAU PROVINCE - Simanjuntak, Josua; Siregar, Sofyan Husein; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This research was conducted in March 2023, located in Koneng Beach, Dumai City. The purpose of this study was to determine the organic matter content and abundance of epipelic diatoms vertically and to analyze the relationship between the organic matter content in sediments and the abundance of epipelic diatoms vertically in the intertidal area of Dumai City Waters. The method used is the survey method. The sampling point is determined using a purposive sampling method. Sampling of epipelic diatoms was carried out using a modified corer, which was then brought to the laboratory to identify and calculate the abundance of diatoms and the sediment samples to calculate the content of organic matter and sediment fractions. Water quality measurements accompanied sampling with a brightness value of 0.57 m, temperature of 33 °C, current speed of 0.33 m/s, salinity of 28 ppt, and pH of 8.13. The results of the analysis of organic matter are 2.55 – 13.38%. The results of the sediment fraction analysis show that the research location is dominated by sandy silt. Nineteen genera of epipelic diatoms were found in the waters of Koneng Beach, Dumai City, with abundance values between 5,291–39,983 ind/cm2. The one-way ANOVA test results obtained an average value of 0.000, meaning there is a significant difference in the abundance of epipelic diatoms between the sediment layers. The results of the linear regression test showed that the effect of sediment organic matter on the abundance of epipelic diatoms was 50.85%.